Intraoperative bronchial blood flow evaluation using indocyanine green fluorescence for bronchoplasty: A case report. (March 2021) - Kawamoto, Nobutaka; Okita, Riki; Hayashi, Masataro; Suetake, Ryo; Murakami, Tomoyuki; Inokawa, Hidetoshi
Highlights: Indocyanine green fluorescence (ICG-FL) detects blood flow of the bronchial artery. ICG-FL is effective for blood flow evaluation after bronchial artery embolization. Bronchial blood flow evaluation may reduce the risk of anastomotic leakage. Abstract: Introduction and importance: Blood flow evaluation of bronchial arteries using indocyanine green fluorescence (ICG-FL) is rarely reported during pulmonary resection. We present the case of a patient with bronchiectasis and a history of bronchial artery embolization (BAE) for hemoptysis. Bronchial artery blood flow was evaluated using ICG-FL during lobectomy with bronchoplasty. Case presentation: A 63-year-old woman presented with right middle lobe bronchiectasis (due to nontuberculous mycobacteriosis) and repeated hemoptysis, which had previously been corrected each time with hemostasis by BAE. Bronchoscopy revealed a swollen blood vessel proximal to the right middle lobe bronchus that was suspected of being the origin of bleeding. Right middle lobectomy with bronchoplasty was performed to prevent hemoptysis. ICG-FL was used to detect the patency of the right bronchial arteries, and the arteries surrounding the right middle lobe bronchus were ligated. The proximal side of the right middle lobe bronchus was cut in a deep wedge shape, and the bronchus was anastomosed. ICG-FL revealed that the blood supply was maintained at the bronchial anastomosis. No bronchial anastomotic leakage was observed after the surgery. Clinical discussion: The key to successful bronchoplasty is the maintenance of blood flow. Bronchial artery blood flow theoretically decreases after BAE. In this case, ICG-FL was able to detect bronchial artery patency before cutting the bronchus as well as the maintenance of blood flow at the bronchial anastomosis after bronchoplasty. Conclusion: Intraoperative blood flow evaluation of the bronchus using ICG-FL may reduce the risk of bronchial anastomotic leakage caused by ischemia after bronchoplasty.